Stoning Law and Human Rights - Abdullah; Muntasir; Safrizal (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The law contained in Islam can provide values and an essential sense of justice for all Muslim and non-Muslim human beings. One of the laws in Islam is stoning. Adultery is an act that has been forbidden by Allah and is included in a big and very heinous sin. The application of the law of stoning was first applied in Islam before the conquest of Mecca (fathul Mecca), and before the revelation of Surah An-Nur verse 2 regarding vols (whips), Most scholars agree that for adulterers who are muhsan the punishment is death by being stoned with stones or the like. However, there is no reference that states that the type of stoning law violates human rights or does not violate human rights, but the highlight here is the stoning (death) punishment. Whether the death penalty violates human rights or not, this becomes a controversy between one party and another who has a different perspective, the concept of human rights in Islam is different from the concept of human rights in the perspective of western countries.